Social relevance of the Quezon City Public Library System - Almoniña, John Ronald R.; Paragua, Jor-el E.; Obille, Kathleen Lourdes B. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2013)
Public libraries are tasked to provide materials, programs, and services that cater to the needs of the community that it serves. It is the responsibility that serves to establish the public libraries as being socially significant and relevant. This study aimed to discover the extent of the Quezon city Public Library's significance to society based on its perceived effect in terms of these major social impact indicators: 1) Basic Literacy; 2) Business/Career; 3) The Library as a place; 4) Information Literacy; 5) General Information; 6) Empowerment; 7) Health and Well Being; 8) Personal Development; 9) Social Cohesion; and 10) Imagination/Creativity.
The study used the survey method for its research design. Structured questionnaires were distributed to the librarians, library staff, and active and potential users of the QCPL, the samples of which were identified through convenience sampling. The main findings of the study showed that the respondents' overall perception on the QCPL's capability to meet its stated goals and objectives was positive, with most respondents agreeing or strongly agreeing. The respondents' overall perception of the effect of the QCPL on society based on the given social impact indicators was seen as slight to moderate. Also of note was the respondents positive perception on the QCPL's capability to provide library and information services responsive to the needs of the community based on most of them indicating agreement or strong agreement. Lastly, the respondents perceive the QCPL to have strongly met its stated goal and objective of providing facilities and technology for information access and retrieval.
Recommendations of the study include improving the overall quality of the QCPL's branch libraries and bringing them up to a uniform level. Further studies on the community's needs are also encouraged to better understand the QCPL's contribution to society. Finally, the study itself may be undertaken on other public libraries to assess the overall social relevance of the public libraries in the Philippines.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Quezon City Public Library System -- Social aspects